2019
DOI: 10.3390/molecules24234353
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenes and Aromatic Meroterpenoids with Antioxidant Activity and Neuroprotective Effects from Ganoderma lucidum

Abstract: Reactive oxygen/nitrogen species generated in the human body can cause oxidative damage associated with many degenerative diseases such as atherosclerosis, dementia, coronary heart diseases, aging, and cancer. There is a great interest in developing new antioxidants from Ganoderma fungus due to its low toxicity. As part of our ongoing search for antioxidative constituents from the fruiting bodies of Ganoderma lucidum, the chemical constituents were investigated and seven secondary metabolites, including one ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 38 publications
(43 reference statements)
1
54
0
2
Order By: Relevance
“…Terpenoids are previously reported to possess multi-faceted neurological properties because of their antioxidant properties. 57 Phytols, the major detected terpenoids, are testified to exert prominent antioxidant action by activating superoxide dismutase and restoring the glutathione metabolizing enzyme system. Furthermore, recently it has been reported that phytol, can mitigate the scopolamine-induced cognitive deficit by repressing the activity of cholinesterases in the brains of Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Terpenoids are previously reported to possess multi-faceted neurological properties because of their antioxidant properties. 57 Phytols, the major detected terpenoids, are testified to exert prominent antioxidant action by activating superoxide dismutase and restoring the glutathione metabolizing enzyme system. Furthermore, recently it has been reported that phytol, can mitigate the scopolamine-induced cognitive deficit by repressing the activity of cholinesterases in the brains of Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…ABTS forms stable radicals when it reacts with potassium persulfate, which has the absorbance maxima at wavelength 734 nm. The addition of antioxidants decreases the absorbance at 734 nm since the antioxidants inhibit the formation of ABTS radicals, thus decreasing its concentration in the solution [37]. Figure 3a shows the scavenging effects of WGNP and WGAP with ascorbic acid as a positive control.…”
Section: Abts Radical Scavenging Activitymentioning
confidence: 99%
“…Hydrogen peroxide concentration is decreased by scavenger compound by facilitating the conversion of H 2 O 2 to H 2 O depending on the antioxidant potential of the component present in the extract [68] . This is due to scavenging activities of triterpenoids, phenolic, and polysaccharide compounds in the ethanolic extract of G. lucidum [69–72] …”
Section: Resultsmentioning
confidence: 99%